Exploring Factors Affecting the Effectiveness of Web-Advertising - Farhan, Mohd.; Yousaf, Anish (Indian Journal of Marketing, 2016)
Social media sites allow companies to enhance customer interaction to a more personal level and enable businesses to build closer relationships with their customers as well as expand the market to the customers whom they could not reach before. For marketers, assessing the effectiveness of their ads on social networking sites is an important area. They need to have a good understanding of factors that can help them to design effective web-ads for gaining maximum profit. The aim of this paper was to explore important factors from customers’ point-of-view for effective web-ads placed on various social networking sites. Purposive sampling was used to collect data with the help of structured questionnaire and factor analysis was used for data analysis. Results of the study revealed five factors which are important for any web-ad to make it more attractive to the target customers. These five factors are named as Web-ad placement, Web-ad Presentation, Web-ad Content, Celebrity in Web-ad, and Web-ad Duration.